The social resistance to homosexuality in McCafe Taipei's advertising - Altobeli Lobodally (Jurnal Komunikasi Profesional, 2022)
Advertising is not a tool to sell a product. The ideology that has been carried by the advertising creator is used to resist the common ideology. Homosexuality isstill thought of as a sexual deviation and a crime. This research’s purpose is to disassemble the homosexuality in the Taipei McCafe’s advertising. Thisresearch is using popular culture, and Barthes’s analysis. From the second order of signification (denotation, connotation, and myth) it is shown that havinga gay son is a shame condition for a parent commonly. It is a hard situation for each parent to find out that his son loves a guy too. Through this study, theresearcher also found that homosexuals are part of the family whose existence must be accepted by parents. Homosexuals in this advertisement areconsidered as people who can determine their right to choose their partners and can be accepted as part of the family. In the beginning, advertising is only atool to sell the product, but this situation shows that becoming gay is a common thing. Homosexuality is just the sexual preference. Homosexuality it is not asexual deviation. So, parent nowadays, has to accept their son’s sexual preference. From this advertising, the advertisers are trying to resist the ideology about refusing the homosexuality.